Peran Majelis Dalam Membentuk Solidaritas Sosial : Studi Perspektif Emile Durkheim - Hamdan Shofiyullah (DIALEKTIKA, 2025)
This study aims to examine the role of the assembly in forming social solidarity in local communities using Émile Durkheim's perspective. This study was conducted at the Majelis Sholawat Nariya, Prekbun Village, through a qualitative approach with observation techniques, in-depth interviews, and documentation. The results of the study indicate that the routine activities of the assembly carried out in rotation at members' homes not only strengthen religious values, but also form close social relations among members. This finding indicates the formation of mechanical solidarity, marked by similarities in activities, values, and habits carried out collectively. On the other hand, the development of the role of the assembly into the social realm such as mutual cooperation and cross-community activities also shows the emergence of organic solidarity, namely cooperation that arises from the differentiation of social roles and functions. This study presents novelty by showing that traditional institutions such as the assembly still have vitality and relevance in building social cohesion in modern society. The assembly has proven to be an effective alternative social space in dealing with the crisis of social alienation and individualism. This finding provides a theoretical contribution to strengthening Durkheim's theory in the local context, as well as practical implications for the development of community-based social institutions.